Light‐Emitting Diode Visible‐Light‐Driven Photocatalytic Redox Reactions in Nitrogen Oxide Removal Using β‐Bi2O3/Bi/g‐C3N4 Prepared by One‐Step In Situ Thermal Reduction Synthesis - Qin, Xing; Tan, Huaqiao; Zhao, Yingnan; Cheng, Sihang; Zhou, Min; Lin, Jinliang; Ho, Wing-Kei; Li, Haiwei; Lee, Shun-Cheng (Advanced energy and sustainability research, 2023)
Traditional photocatalytic oxidation of nitrogen oxide (NO) may cause the more toxic NO2 generation after longtime reaction, and even the ideal final production nitrate may also inevitably cause the poisoning of photocatalysts. Thus, utilizing photocatalytic reduction to remove NO into N2 should be considered more practical but is still challenging currently. Herein, a novel S‐scheme β‐Bi2O3/Bi/g‐C3N4 heterojunction photocatalyst is developed via a one‐step in situ thermal reduction method. The photocatalytic degradation efficiency over this S‐scheme photocatalyst exhibits around 88.7% degradation rate for NO with little NO2 generation under light‐emitting diode light irradiation, which is significantly higher than that of the pristine g‐C3N4 (60%). Interestingly, both reduction of NO into N2 and oxidation of NO into NO3− exist synchronously in the system. The increased degradation efficiency and the efficient reduction pathway occurring should be ascribed to the enhanced generation, separation, and transfer of the photogenerated carriers through the Bi‐bridge S‐scheme heterojunction. This study has provided a new route for regulating the photocatalytic reaction pathway for NO removal through a simple synthesis method. Utilizing photocatalytic oxidation to remove nitrogen oxide (NO) is still limited in practice because of the generated nitrogen dioxide (NO2) and nitrate (NO3−) during the reaction. Herein, a novel S‐scheme heterojunction photocatalyst is developed to reduce NO into nitrogen (N2) and oxidize NO into NO3− synchronously, which provides a new route for regulating the reaction pathway for NO removal.